Ecological determinants of academic achievement: background factors, maternal practices and adolescent academic self-esteem - Abdullah, Aida (2002)
The current study attempts to address the paucity of research in examining the combined effects of adolescent and maternal. background factors, maternal parenting influences as well as the inherent adolescent academic self-esteem (in particular the self-efficacy and the locus of control orientation) on the academic achievement of the adolescent. From an ecological perspective, demographic data on the adolescent and his mother elucidated further the nature of the parent-child dyad. Parenting attributes of demandingness and responsiveness were respectively used to gauge the levels of maternal control and monitoring, and maternal warmth. A third parenting dimension, involvement (Paulson, 1994) was added to detect the degree of maternal interest and participation in the academic pursuits of the adolescent. The information pertaining to the perceptions of parenting, selfefficacy and locus of control were gathered using a group-administered questionnaire.The sample of 280 respondents (145 boys and 135 girls) from intact families were chosen to represent adolescents studying in non-residential schools in the Kuala Lumpur region. Those selected were from two age cohorts (140 Form Two and 140 Form Four students). In the present study, it was of noteworthy importance to state that self-efficacy and locus of control orientation of the adolescent possessed cogent influences on achievement In addition, the family size and the age of the adolescent also significantly predicted the academic achievement of the adolescent In essence, as it had been established that the self-perceptions and age of the adolescent as well as family size produced potent effects on achievement, these findings have farreaching consequences on efforts aimed at enhancing the academic success of adolescents.